2022
DOI: 10.23887/jppp.v6i1.46368
|View full text |Cite
|
Sign up to set email alerts
|

Bahan Ajar Digital Interaktif Berbasis Problem Based Learning Materi Keragaman Budaya

Abstract: Guru belum mampu mengembangkan bahan ajar yang bervariasi untuk proses pembelajaran. Hal ini berdampak pada hasil belajar IPS pada siswa yang rendah. Tujuan penelitian ini yaitu mengembangkan bahan ajar digital berbasis problem based learning materi keragaman budaya pada pembelajaran IPS siswa kelas IV. Penelitian ini merupakan jenis penelitian pengembangan dengan menggunakan model pengembangan ADDIE. Metode yang digunakan yaitu non-tes yang berupa lembar kuesioner. Uji kelayakan produk pada penelitian ini dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
0
14
0
7
Order By: Relevance
“…The results showed that the development of digital teaching material in the South Sumatra Traditional Games course was based on validity tests from experts, namely from the material aspect, language aspect, and media aspect, it obtained the Very Good category from the indicators of content eligibility, presentation eligibility, a language component, graphic eligibility, and display eligibility. Based on the analysis results obtained from experts, several suggestions are used as reference material for improving the digital teaching material being developed (Sari et al, 2022). Furthermore, the digital teaching material produced was field tested through 3 (three) stages, namely the one-to-one trial stage, which was carried out on 6 (six) students, small group trials, which were carried out on 15 (fifteen) students, and field tests conducted on 20 (twenty) students.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the development of digital teaching material in the South Sumatra Traditional Games course was based on validity tests from experts, namely from the material aspect, language aspect, and media aspect, it obtained the Very Good category from the indicators of content eligibility, presentation eligibility, a language component, graphic eligibility, and display eligibility. Based on the analysis results obtained from experts, several suggestions are used as reference material for improving the digital teaching material being developed (Sari et al, 2022). Furthermore, the digital teaching material produced was field tested through 3 (three) stages, namely the one-to-one trial stage, which was carried out on 6 (six) students, small group trials, which were carried out on 15 (fifteen) students, and field tests conducted on 20 (twenty) students.…”
Section: Discussionmentioning
confidence: 99%
“…Temuan penelitian sebelumnya juga menyatakan bahwa E-Book interaktif dapat memudahkan siswa dalam belajar dimanapun (Sari & Airlanda, 2022;Wedayanti & Wiarta, 2022). Temuan penelitian lainnya juga menyatakan bahwa Problem Based Learning dapat meningkatkan berpikir kritis pada siswa (Mella et al, 2022;Wedayanti & Wiarta, 2022). Berdasarkan beberapa penelitian tersebut dapat dikatakan bahwa pengembangan E-Book interaktif berbasis Problem Based Learning dapat meningkatkan keaktifan dan berpikir kritis pada siswa.…”
Section: Pendahuluanunclassified
“…Apabila guru menggunakan buku tersebut, hasil belajar siswa mungkin akan meningkat namun kemampuan pemahaman konsep siswa dalam Matematika belum terstimulus dengan sempurna. Oleh karena itu, diperlukan sebuah buku ajar elektronik (e-book) yang memuat aktivitas mengenai konsep yang sesuai dengan tujuan pembelajaran hari ini dan menstimulus kemampuan tersebut (Mella et al, 2022).…”
Section: Pengembangan E-book Berbasis Pemecahan Masalah Untuk Meningk...unclassified